A general theory of minimal increments for Hirsch-type indices and applications to the mathematical characterization of Kosmulski-indices - L., Egghe; Egghe, L. (Malaysian Journal of Library and Information Science, 2017)
Egghe, L. (2014). A general theory of minimal increments for Hirsch-type indices and applications to the mathematical characterization of Kosmulski-indices. Malaysian Journal of Library & Information Science, Vol.19, no. 3: 41-49. For a general function f (n) (n =1,2, ...) , defining general Hirsch-type indices, we can characterize the first increment I1 (n) = (n +1) f (n +1) âˆ’ nf (n) as well as the second increment I2 (n) = I1 (n +1) âˆ’ I1 (n1 +1). An application is given by presenting mathematical characterizations of Kosmulski-indices.